2007
DOI: 10.1007/s10895-006-0152-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Intracellular Delivery of CdTe Quantum Dots (QDs) to Living Cells by Tat Conjugation

Abstract: Quantum dots (QDs), as novel fluorescence probes, have shown a great potential for bio-molecular labeling and cellular imaging. To stain cellular targets, the sufficient intracellular delivery of QDs is required. In this work the tat, a typical membrane-permeable carrier peptide, was conjugated with thiol-capped CdTe QDs to form CdTe Tat-QDs, and the intracellular deliveries of CdTe QDs or CdTe Tat-QDs were compared in human hepatocellular carcinoma (QGY) cells and human breast cancer (MCF7) cells in vitro by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Upon surface modifications, solubility of QDs can be improved making them suitable for biological applications. Further, conjugation with CPPs facilitates cellular uptake of QDs [21,27,51,52]. Though CPPconjugated QDs raise the efficiency of cellular internalization, intracellular distributions of CPP-conjugated QDs have not yet been closely examined.…”
Section: Discussionmentioning
confidence: 99%
“…Upon surface modifications, solubility of QDs can be improved making them suitable for biological applications. Further, conjugation with CPPs facilitates cellular uptake of QDs [21,27,51,52]. Though CPPconjugated QDs raise the efficiency of cellular internalization, intracellular distributions of CPP-conjugated QDs have not yet been closely examined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the modification of the surface of QDs with CPPs improves the labeling rate of cells (37,38). Xue et al (39) developed sulfhydryl-modified QDs combined with the TAT protein to obtain TAT-QD compounds. The QGY liver cancer and the MCF-7 human breast cancer cell lines were cultivated with TAT-QDs and these cells were assessed by laser confocal scanning microscopy (39).…”
Section: Discussionmentioning
confidence: 99%
“…Xue et al (39) developed sulfhydryl-modified QDs combined with the TAT protein to obtain TAT-QD compounds. The QGY liver cancer and the MCF-7 human breast cancer cell lines were cultivated with TAT-QDs and these cells were assessed by laser confocal scanning microscopy (39). The penetration of TAT-QDs into the QGY and MCF-7 cells was observed to increase compared with unmodified QDs, by 2.1 and 1.5 times, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Xue et al, for instance, conjugated Tat peptide to thiol capped CdTe QDs (2-4 nm in diameter) and compared their effectiveness in intracellular delivery to unmodified CdTe QDs in human hepatocellular carcinoma (QGY) cells and human breast cancer (MCF7) cells by means of confocal laser scanning microscopy. The authors were able to demonstrate that the conjugation of Tat enhanced intracellular delivery in both cell lines [85]. The same holds true for the PEG-encapsulated CdSe-ZnS QDs, which were functionalized with covalently bound Tat in order to achieve efficient uptake into mesenchymal stem cells [86].…”
Section: Delivery Of Nanoparticles Using Cpps Quantum Dotsmentioning
confidence: 99%